Wired Enzymes in mesoporous materials: A benchmark for fabricating biofuel cells - Catalano, Paolo Nicolás (2015)
Evolution of fuel cells using metallic inorganic catalysts has led to the development of biofuel cells with potential applications in implantable devices. However, the main disadvantages in real world applications of enzymatic biofuel cells are short lifetime and low power density. Many efforts have been devoted to immobilize redox enzymes on surfaces to allow efficient electrical communication with electrodes and to provide an adequate habitat for biochemical activity. In this context, nanocavities of mesoporous materials offer a tailored environment for protein immobilization. Mesostructured platforms with high surface area and stability have been developed to enhance mass transport, charge transfer from biocatalysts to electrodes and enzyme stability, leading to biofuel cells with improved power density (up to 602 μW cm− 2 at physiological conditions) and overall performance (high stability after 30 h of continuous operation and after 10 days of storage). This review discusses recent developments using mesoporous materials as novel platforms for effective electronic charge transfer in the context of current and emerging technologies in enzymatic fuel cell research, emphasizing their practical implications and potential improvements leading to a major impact on medical science and portable electronics.